Democratic regression and the rise of electoral illiberalism in Indonesia: A multi-dimensional analysis (1998-2024) - Paryanto Paryanto; Hasnan Bachtiar; Faisal Faisal; Christine B. Tenorio (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
Since the political transition of 1998, Indonesia has been widely regarded as a leading case of democratic consolidation in Southeast Asia. However, recent empirical indicators reveal a persistent decline in civil liberties, political pluralism, and institutional accountability. This article examines whether Indonesia is experiencing democratic regression and investigates the emergence of electoral illiberalism as a durable regime trajectory rather than a temporary fluctuation. Methodologically, this study employs qualitative thematic-narrative analysis, triangulating constitutional amendments, electoral laws, Constitutional Court decisions, and executive regulations with international democracy indices, including the Economist Intelligence Unit and Freedom House, from 1998 to 2024. This approach enables a longitudinal assessment of institutional and normative transformations across key democratic dimensions. The findings demonstrate that democratic regression in Indonesia is not marked by the collapse of electoral competition, but by the weakening of horizontal accountability, erosion of the rule of law through systemic corruption, contraction of civic space, and strategic mobilization of majoritarian identity politics. These dynamics reveal how electoral continuity coexists with substantive democratic erosion. This article contributes to debates on democratic backsliding by showing that Indonesia’s trajectory has consolidated into electoral illiberalism, challenging linear models of democratic consolidation and highlighting the limits of electoral democracy.